2018
DOI: 10.1002/navi.249
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Machine Learning VDM for UAVs in GNSS-denied Environment

Abstract: This paper presents a novel approach to enhance unmanned aerial vehicle (UAV) autonomous navigation, without adding extra load to the vehicle. The proposed approach employs the UAV vehicle dynamic model to aid the navigation estimation in a Global Navigation Satellite Systems (GNSS)‐denied environment, without the need to model any part of the UAV, and avoids the requirement for special equipment during the modeling procedures typically required for vehicle dynamic model‐aided navigation. Taking advantage of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…Zahran et al [32] investigates the use of hybrid machine learning to train a VDM and enhance inertial navigation accuracy during periods of GNSS outage using low-cost inertial sensors in a quadcopter. The machine learning module (regression and classification) acts as a substitute, providing a position and velocity solution during periods of GNSS outage.…”
Section: Solutionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Zahran et al [32] investigates the use of hybrid machine learning to train a VDM and enhance inertial navigation accuracy during periods of GNSS outage using low-cost inertial sensors in a quadcopter. The machine learning module (regression and classification) acts as a substitute, providing a position and velocity solution during periods of GNSS outage.…”
Section: Solutionsmentioning
confidence: 99%
“…The proposed architecture is preferred over the model-aided architectures [18,26,32] for a number of reasons. In low-cost applications, the quality of the inertial sensors used is relatively low and inherently affected by significant noise sources.…”
Section: Solutionsmentioning
confidence: 99%
“…Also, they showed that the inclusion of the VDM parameters and wind in the state vector improved the stability of the filter and reduced error growth, especially in the presence of VDM parameter errors and wind. Zahran et al [13] derived a VDM from a hybrid machine learning scheme utilising a bagged regression and classification technique to aid an INS during a GNSS outage. The approach showed significant improvements in position estimation during an outage.…”
Section: Introductionmentioning
confidence: 99%
“…The vast majority of VDM integration schemes in the literature rely on using filtered GNSS measurements output by a GNSS receiver to provide a bounded navigation solution. Filtered measurements from a GNSS receiver are usually not available during a GNSS outage or when tracking less than four satellites, which can cause the navigation solution to drift even when using a VDM [9]- [11], [13], [16]. Further, model-aided INS schemes can easily be disabled in case of IMU failure and additionally, multi-process model schemes introduce duplicate states that increase computational cost [17].…”
Section: Introductionmentioning
confidence: 99%
“…The state prediction of the dynamic model and INS are fused, and the procedure of the traditional Kalman filter is simplified. A dynamic model/INS/GPS fusion scheme was proposed by [23]. When GPS is available, the INS/GPS fusion results are used to identify the model parameters.…”
Section: Introductionmentioning
confidence: 99%